UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI STRATEGI EVERYONE IS A TEACHER HERE PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Mukhlis, Mukhlis (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2016)
Learning activities required method or strategy to facilitate teachers in presenting the material to learners. Relates to a method of learning that has significance with regard to the way in which the teacher in delivering learning materials to learners. So in this discussion will explain how an increase in Student Results Through Strategy Everyone Is A Teacher Here in the Subject of Islamic education in the hope of providing solutions to problems that arise in the learning activities, and is expected to provide an important role in the learning process. Here is also an explanation of how the implementation of the learning process through Strategy Everyone Is A Teacher Here are carried out in accordance with kaedah-kaedah applicable to the use of Strategy Everyone Is A Teacher Here are, and the things that must be considered a teacher in the choice of teaching methods such as the relevance of the method by state students, the relevance of the method with the ability of teachers, the relevance of the method with material / subject matter, the relevance of the learning objectives and methods with others.